Aphyllophoroid funga (Basidiomycota) of Finland: range extensions and records of nationally new and rare species - Panu Kunttu; Teppo Helo; Matti Kulju; Jari Julkunen; Jorma Pennanen; Anton G. Shiryaev; Hannu Lehtonen; Heikki Kotiranta (Acta Mycologica, 2019)
Knowledge of the Finnish aphyllophoroid funga has increased substantially in recent years. In this article, we present two species new to Finland: Spiculogloea subminuta Hauerslev and Typhula suecica I. Olariaga, G. Corriol, I. Salcedo & K. Hansen, and document Sistotrema luteoviride Kotir. & K.-H. Larss. for the third time globally. We also contribute 50 new records of 33 nationally rare species (with a maximum of ten previous records in Finland) and list 52 regionally new species, found for the first time in a certain subzone of the boreal vegetation zone in Finland. Each record is enclosed and contains notes on the substrate. Furthermore, the ecology of the nationally new species and the distribution of rare species are discussed.